THE EFFECT OF FINANCIAL DISTRESS, DEBT DEFAULT, PROFITABILITY, AND THE PREVIOUS YEAR’S AUDIT OPINION ON THE ISSUANCE OF A GOING CONCERN OPINION: A Case Study of Transportation and Logistics Companies Listed on the Indonesia Stock Exchange from 2019-2023 - Jenny Almas Yuwandi; Ariyani; Nila Sari; Putri Zanufa Sari; Ibnu Fajarudin; RR Prastoeti; Emiliya Rahma Wati (Ekomania, 2026)
Going concern refers to the company's ability to maintain its operations for more than one year. This is an important factor in determining the survival of the company and is a basic assumption in the preparation of financial statements. This study aims to explore the factors that influence going concern audit opinion in companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. Research data was obtained from the company's financial and annual reports through the systematic documentation method on the official IDX website. Data analysis was carried out using regression models to test the effect of financial distress, debt default, profitability, and previous year's audit opinion on going concern audit opinion. The results showed that individually, financial distress, debt default, and profitability had no significant effect on going concern audit opinion, with a significance value of 0.635; 0.815; and 0.915, respectively. In contrast, the previous year's audit opinion has a significant positive effect with a significance value <0.001. Simultaneously, the F test results show a value of 18,501 with a significance of <0.001, which indicates that the regression model has a significant contribution to going concern audit opinion.